What's Across the Border? Re-Evaluating the Cross-Border Evidence on Minimum Wage Effects - Priyaranjan Jha; David Neumark; Antonio Rodriguez-Lopez (Center for Economic Studies and ifo Institute (CESifo), 2022)
Dube, Lester, and Reich (2010) argue that state-level minimum wage variation can be correlated with economic shocks, generating spurious evidence that higher minimum wages reduce employment. Using minimum wage variation within contiguous county pairs that share a state border, they find no relationship between minimum wages and employment in the U.S. restaurant industry. We show that this finding hinges critically on using cross-border counties to define local economic areas with which to control for economic shocks that are potentially correlated with minimum wage changes. We use, instead, multi-state commuting zones, which provide superior definitions of local economic areas. Using the same within-local area research design-but within cross-border commuting zones-we find a robust negative relationship between minimum wages and employment.
Keywords: J23; J38; 330; minimum wage; employment; commuting zones